Selective inhibition of cullin 3 neddylation through covalent targeting DCN1 protects mice from acetaminophen-induced liver toxicity - Haibin Zhou (Nature Portfolio, 2021)
Activation of cullin-RING ligases can be inhibited by targeting DCN1, but selective DCN1 inhibitors with in vivo activity are lacking. Here, the authors develop covalent DCN1 inhibitors that selectively and potently inhibit cullin-3 activation and downstream functions in cells and in mice.